The effect of pre-oxidation parameters on the corrosion behavior of AISI 441 in dual atmosphere. (2nd August 2018) - Goebel, Claudia; Alnegren, Patrik; Faust, Robin; Svensson, Jan-Erik; Froitzheim, Jan
Abstract: Dual atmosphere conditions have been shown to be detrimental for the ferritic stainless steel interconnects used in solid oxide fuel cells (SOFC) under certain conditions. In the present work, we analyze the influence of pre-oxidation on corrosion resistance in dual atmosphere with regard to two parameters: the pre-oxidation time and the pre-oxidation location (pre-oxidation layer on the air-facing side or the hydrogen-facing side). The steel AISI 441 is investigated and pre-oxidation is achieved in air at 800 °C. To examine the influence of pre-oxidation time on corrosion behavior, five different pre-oxidation times are used: 0, 11, 45, 180, and 280 min. The samples are exposed discontinuously to dual atmosphere for 1000 h at 600 °C. Photographs, taken throughout the exposure, show that the pre-oxidation time correlates with the onset of breakaway corrosion. To analyze the influence of pre-oxidation location on corrosion behavior, the samples are pre-oxidized for 180 min, and then a pre-oxidation layer is removed from one side of the sample. Subsequent dual atmosphere exposure at 600 °C for 500 h shows that the pre-oxidation layer on the hydrogen-facing side is more important for corrosion resistance in dual atmosphere than the pre-oxidation layer on the air-facing side. Highlights: Pre-oxidized AISI 441 is exposed to dual atmosphere for up to 1000 h. Beneficial effect of pre-oxidation on corrosion behavior is observed. Shorter pre-oxidation times lead to earlier material failure. Pre-oxidation layer on H2 -facing side is more important for corrosion resistance.